Improving Students’ Vocabulary By Using Team Assisted Individually (TAI) And Cooperative Integrated Reading And Composition (CIRC) Method - Mardin Silalahi; Benarita; Warmanto Turnip (Program Studi Pendidikan Bahasa Inggris FKIP, 2024)
The aim of this research is to analyze the improvement of students’ vocabulary by using team assisted individually (TAI) and cooperative integrated Reading and composition (CIRC) method. The researcher carried out at the eight grade of SMP N 1 Dolok Pardeamean. This research used the quantitative approach with an experimental design by using the one-group design by cluster sampling technique for choosing 30 students and every student would give the pre-test and post-test for data collection. The technique of collecting the data is by using the statistic application called SPSS 21.0 version. Based on the result of the hypothesis testing that the T-counted is greater than T-table (Tcounted = 9,543 > Ttable = 1,699). This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted it can be conclude that the TAI and CIRC method is effective for improving students' vocabulary, as evidenced by the rejection of the null hypothesis and acceptance of the alternative hypothesis based on statistical analysis. The conclusion of this research is that the used of the TAI and CIRC is effective because it involves collaborative reading, discussion, and writing activities that help learners engage with and internalize new words and concepts